2021
DOI: 10.1108/rpj-06-2021-0136
|View full text |Cite
|
Sign up to set email alerts
|

Towards 3D printing of a monocoque transtibial prosthesis using a bio-inspired design workflow

Abstract: Purpose There are over 40 million amputees globally with more than 185,000 Americans losing their limbs every year. For most of the world, prosthetic devices remain too expensive and uncomfortable. This paper aims to outline advancements made by a multidisciplinary research group, interested in advancing the restoration of human motion through accessible lower limb prostheses. Design/methodology/approach Customization, comfort and functionality are the most important metrics reported by prosthetists and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The device was printed in an FDM printer using PLA and PETG (Polyethylene terephthalate glycol) for diagnostic purposes and PA-12 (Polyamide) for end-use purposes. The authors reported that by using the digital workflow and 3D printing technique, they were able to reduce the average cost, weight, and time of production by 95%, 55% and 95%, respectively as compared to traditional prosthetic devices [ 34 ]. It should also be noted that this reduction of cost is mainly for the fabrication of the socket, other components are still needed to be connected to the socket to make a complete prosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The device was printed in an FDM printer using PLA and PETG (Polyethylene terephthalate glycol) for diagnostic purposes and PA-12 (Polyamide) for end-use purposes. The authors reported that by using the digital workflow and 3D printing technique, they were able to reduce the average cost, weight, and time of production by 95%, 55% and 95%, respectively as compared to traditional prosthetic devices [ 34 ]. It should also be noted that this reduction of cost is mainly for the fabrication of the socket, other components are still needed to be connected to the socket to make a complete prosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The design and manufacturing time using AM technologies included: data acquisition (1 h), design time (3 h) and printing time (12 h). The total prostheses development time was 16 h (De Vivo Nicoloso et al , 2021). Rapid manufacturing machine is introduced to further reduce the printing time in FDM.…”
Section: Additive Manufacturing In Prosthesesmentioning
confidence: 99%
“…The development of digital cameras and the accompanying transition to digital photogrammetry has led to technologies for the reconstruction of 3D models using photogrammetric algorithms [18]. Digital photogrammetry has been used successfully to reconstruct patient anatomy in many medical contexts such as cranial deformation scanning [8], [9], [19], facial scanning [10], [11], [20], and amputated limb scanning [3], [5]- [7].…”
Section: A Photogrammetry For Medical Imagingmentioning
confidence: 99%